Tau protein, phosphorylated tau protein, and beta-amyloid 42 levels in patients with neurodegenerative diseases complicated by cognitive deficits A non-randomized, concurrent, case-control investigation - Radomir Talab Jiri Masopust Ctirad Andrys Pavel Stourae Jakub Hort Martin Valis (Neural regeneration research, 2009)
BACKGROUND： The differential diagnosis of many neurodegenerative disorders depends primarily on clinical symptoms together with imaging methods. Recently, increased importance has been placed on the use of biomarkers for diagnosing various neurodegenerative disorders. OBJECTIVE： To assess the feasibility of tau-protein, phosphorylated tau-protein, beta-amyloid 42 （Aβ42）, and 14-3-3 protein as biomarkers for diagnosing several neurodegenerative diseases complicated by cognitive deficits. DESIGN, TIME AND SETTING： A non-randomized, concurrent, case-control investigation was performed in three medical centers in the Czech Republic （Department of Neurology at the University Hospital in Hradec Kralove, Department of Neurology at the 2rd Medical Faculty, and the University Hospital Motol） between October 2000 and November 2006. PARTICIPANTS： Eighteen patients with probable AIzheimer＇s disease, 4 patients with Creutzfeldt-Jakob disease, 10 patients with frontotemporal dementia, 9 patients with clinically isolated syndrome suggestive of multiple sclerosis, and 7 patients with multiple sclerosis, as well as 38 race-, nationality-, and age-matched cognitively intact controls, were included in the study. Diagnoses were established based on the following criteria： the criteria for Alzheimer＇s disease proposed by the National Institute of Neurological and Communicative Disorders and Stroke/Alzheimer＇s Disease and Related Disorders Association, WHO criteria for Creutzfeldt-Jakob disease, Neary criteria for frontotemporal dementia, and McDonald＇s criteria for multiple sclerosis. All included patients were confirmed to suffer from various degrees of dementia. METHODS： Enzyme-linked immunosorbent assay was used to measure concentrations of tau-protein, phosphorylated tau-protein, and Aβ42 in cerebrospinal fluid （CSF） samples collected by standard lumbar puncture from each patient. Moreover, 14-3-3 protein was assessed by Western blot in CSF of Creutzfeldt-Jakob disease patients. Cognitive status was assessed using the Mini Mental Scale Examination （MMSE） in all subjects. MAIN OUTCOME MEASURES： Establishment of biomarkers with greatest specificity and sensitivity for the investigated disorders according to Receiver Operating Characteristic curves, which were based on values from patients and controls; correlation between concentrations of given biomarkers and demographic parameters, diagnosis, duration of disease, and level of cognitive deficit. RESULTS： Increased concentrations of total tau protein and phosphorylated tau protein, and decreased levels of Aβ42, in CSF of Alzheimer＇s disease patients reached the required sensitivity/specificity ratio of 80% or greater. A marked elevation in CSF concentrations of total tau protein showed even greater sensitivity than 14-3-3 protein in Creutzfeldt-Jakob disease. There was no association between selected biomarkers and frontotemporal dementia or multiple sclerosis. Phosphorylated tau-protein was the only biomarker that noticeably correlated with MMSE scores for Alzheimer＇s disease.CONCLUSION： Levels of total tau protein, phosphorylated tau protein, and A!342 in the CSF could differentiate patients with Alzheimer＇s disease and Creutzfeldt-Jakob disease from healthy controls and patients with other neurodegenerative disorders. The diversity of absolute values demonstrates the necessity to establish a specific standard for each laboratory.